Symbiosis of cornulitids with the cystoporate bryozoan Fistulipora in the Pridoli of Saaremaa, Estonia. (11th May 2020) - Vinn, Olev; Ernst, Andrej; Wilson, Mark A.; Toom, Ursula
Abstract : Cornulites sp. and Fistulipora przhidolensis formed a symbiotic association in the Pridoli (latest Silurian) of Saaremaa Island, Estonia. This Cornulites sp.– F. przhidolensis association is the youngest example of cornulitid–bryozoan symbiosis. Symbiosis is indicated by intergrowth of both organisms. The cornulitids are completely embedded within the cystoporate bryozoan colony, leaving only their apertures free on the growth surface of bryozoan. In terms of food competition, this association could have been slightly harmful to F. przhidolensis as Cornulites sp. may have been a kleptoparasite. There may have been a small escalation in the evolution of the endobiotic life mode of cornulitids as the number of such associations increased from the Ordovician to Silurian. It is likely that Palaeozoic bryozoan symbiosis reached its maximum in the Late Ordovician. Most of the symbiotic bryozoans in the Palaeozoic are trepostomes, and the diversity of symbiotic associations was also greatest among trepostomes.